Structural features and relaxation properties of PET/PC blends containing impact strength modifier and chain extender (eXPRESS Polymer Letters)
It has been investigated how methylene diphenyl diisocyanate (MDI) influences the morphology, rheological, mechanical and relaxation properties, as well as PET crystallizability, of PET/PC/(PP/EPDM) ternary blends produced by the reactive extrusion process. It appears that irrespective of phase structure of the blends, MDI causes a rise in melt viscosity (decreased MFI-values) of the material which is the result of an increased molecular weight of the macromolecules; PET crystallization becomes retarded. MDI improves compatibility between PET and PC in PET/PC/(PP/EPDM) ternary blends. Addition of MDI leads to higher values of the dynamic shear modulus for PET high elastic state (in the temperature range between Tg PET and cool crystallization temperature of PET); the PET cool crystallization and melt crystallization processes become retarded; the PET and PC glass transition temperatures approach one another. MDI has been shown not to influence significantly the blend morphology or the character of interaction between the PP/EPDM disperse phase and PET/PC blend matrix.